Metabolic health and global cardiovascular risk in obese patients. Endocrinology Service. Cienfuegos, 2021-2022 - Leonelsy Núñez García; Elodia María Rivas Alpízar (Medisur)
Foundation: The overweight and obesity increasing prevalence, two important components of metabolic syndrome, represents a serious health risk. Objectives: relate the factors associated with metabolically healthy and unhealthy obese people and estimate the global cardiovascular risk in both groups. Methods: a descriptive, cross-sectional correlational study was carried out in 112 patients aged 18 years or older with a diagnosis of obesity that were looked after in the Endocrinology Service Nutrition Consultation of the Gustavo Aldereguía Lima University Hospital, in Cienfuegos, from May 2021 to May 2022. The analyzed variables were: age, sex, dietary habits, lifestyle, phenotype (metabolically healthy and unhealthy). Results: The frequency of metabolically healthy obese people was 35% and that of unhealthy people was 65%. Both groups frequently consume fruits and vegetables. 91.1% consumed sugary drinks and 85.7% did not practice physical exercise, without statistical significance. A significant association was evident between global cardiovascular risk and the condition of having a metabolically unhealthy obese phenotype compared to healthy people. Conclusions: the metabolically unhealthy obese phenotype was shown in more than half of the studied participants; the interaction of biological elements with unhealthy lifestyle is related to global cardiovascular risk in the metabolically unhealthy obese phenotype regarding the healthy.